What About Passion in Education? The Concept of Passion, why it is Important and How Teachers Can Promote it - Ruiz-Alfonso, Zuleica; Vega, Lidia Santana; Beltran, Elina Vilar (European Scientific Journal, ESJ, 2018)
Is passion important in the educational context? What are the benefits of passion? Is it possible to foster students’ passion? What are the teachers’ characteristics or behaviors that foster students’ passion? The aim of this study was to answer this questions by a literature review, as well as to present a global and current picture about the role of passion in Education. Although research on passion is really recent and, therefore, still scarce, the literature reviewed showed a great variety of passion’s outcomes, which highlights the importance it has in the educational context. We also tried to summarize the teachers’ characteristics studied up to now that can foster the students’ passion. We concluded by presenting the potential implications of the articles reviewed within education, and presenting the main conclusions of the review.